2009
DOI: 10.1186/1476-4598-8-123
|View full text |Cite
|
Sign up to set email alerts
|

The sonic hedgehog signaling pathway is reactivated in human renal cell carcinoma and plays orchestral role in tumor growth

Abstract: BackgroundHuman clear cell renal cell carcinoma (CRCC) remains resistant to therapies. Recent advances in Hypoxia Inducible Factors (HIF) molecular network led to targeted therapies, but unfortunately with only limited clinical significance. Elucidating the molecular processes involved in kidney tumorigenesis and resistance is central to the development of improved therapies, not only for kidney cancer but for many, if not all, cancer types. The oncogenic PI3K/Akt, NF-kB and MAPK pathways are critical for tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 33 publications
7
86
1
1
Order By: Relevance
“…Consequently, Sjolund et al (2008) and Hueber et al (2006Hueber et al ( , 2008 have shown that the developmental Notch signaling cascade and Pax2, critical for nephrogenesis, are constitutively active in human CCC cell lines and have growth-promoting effect. More recently, we have reached similar conclusions concerning the involvement of the developmental sonic hedgehog (SHH) signaling pathway in human CCC progression, and we showed further that the SHH signaling pathway has orchestral roles in the activation of oncogenic pathways in this disease, including the phosphoinositide kinase-3 (PI3K)/ Akt, the nuclear factor-kappaB (NF-kB) and mitogenactivated protein kinase (MAPK) signaling pathways (Dormoy et al, 2009). This is particularly important as all these pathways, critical during kidney development (Reidy and Rosenblum, 2009), are constitutively reactivated in CCC tumors (Sourbier et al, 2006Schedl, 2007;Huang et al, 2008).…”
Section: Introductionsupporting
confidence: 49%
See 3 more Smart Citations
“…Consequently, Sjolund et al (2008) and Hueber et al (2006Hueber et al ( , 2008 have shown that the developmental Notch signaling cascade and Pax2, critical for nephrogenesis, are constitutively active in human CCC cell lines and have growth-promoting effect. More recently, we have reached similar conclusions concerning the involvement of the developmental sonic hedgehog (SHH) signaling pathway in human CCC progression, and we showed further that the SHH signaling pathway has orchestral roles in the activation of oncogenic pathways in this disease, including the phosphoinositide kinase-3 (PI3K)/ Akt, the nuclear factor-kappaB (NF-kB) and mitogenactivated protein kinase (MAPK) signaling pathways (Dormoy et al, 2009). This is particularly important as all these pathways, critical during kidney development (Reidy and Rosenblum, 2009), are constitutively reactivated in CCC tumors (Sourbier et al, 2006Schedl, 2007;Huang et al, 2008).…”
Section: Introductionsupporting
confidence: 49%
“…We have shown, very recently, by western blot analysis on nine normal/tumoral tissue pairs that Lim1 is almost exclusively reexpressed in tumors (Dormoy et al, 2009). Here, we have considerably extended this analysis.…”
Section: Lim1 Is Exclusively Reexpressed In Human CCC Tumorsmentioning
confidence: 62%
See 2 more Smart Citations
“…20,21,[30][31][32][33][34][35] Furthermore, a vast array of new TAAs with corresponding peptides from HLA class I and II were discovered (Table 3). These included LOX and PLOD2, with high potential in engaging metastasis, [36][37][38] GRB2, ITPR3, and BCAR1, all of which are part of the EGFR pathway 39 and other growth factor receptor pathways, plus ENPEP, NRP2, TGFBI, THBS1, and THBS2, which are essential for angiogenesis.…”
Section: Lc-ms/ms Identifies a High Amount Of Naturally Presented Hlamentioning
confidence: 99%